Quality Is in the Eye of the Beholder: Taste Projection in Markets with Observational Learning - Gagnon-Bartsch, Tristan; Rosato, Antonio (American Economic Review, 2024)
We study how misperceptions of others’ tastes influence beliefs, demand, and prices in markets with observational learning. Consumers infer a good’s quality from the quantity demanded and price paid by others. When consumers exaggerate the similarity between their and others’ tastes, such “taste projection” generates discrepant quality perceptions, which are decreasing in a projector’s taste and increasing in the observed price. These biased inferences produce an excessively elastic market demand. We also analyze dynamic monopoly pricing with short-lived taste-projecting consumers. Optimal pricing follows a declining path: a high initial price inflates future buyers’ perceptions, and lower subsequent prices induce overadoption. (JEL D42, D83, D91, L15)